Portal venous gas and pneumatosis intestinalis: ominous findings with an idiopathic aetiology. Issue 2 (8th February 2019) - Ibrahim, Abdullah; Edirimanne, Senarath
Abstract: Pneumatosis Intestinalis and hepato-portal venous gas are rare but ominous radiological findings that are synonymous with mesenteric ischaemia and bowel infarction in the majority of cases. Very uncommonly benign pathology have been implicated, including respiratory and inflammatory bowel disease. We provide a case of a 69-year-old gentleman with extensive peripheral vascular disease, who presented with generalized abdominal pain and findings of both pneumatosis intestinalis and hepato-portal venous gas. Laboratory investigations were unequivocal, with only mild lactatemia. Emergency laparotomy was performed, which revealed no obvious cause and only some turbid pelvic free fluid. The patient had an uncomplicated recovery. This case illustrates the importance of guiding decisions based on the patient's clinical state, and of keeping an open mind to benign pathology. It also highlights the importance of early surgical intervention in cases of high clinical suspicion.